2005
DOI: 10.1063/1.1895798
|View full text |Cite
|
Sign up to set email alerts
|

Stretching distributions in chaotic mixing of droplet dispersions with unequal viscosities

Abstract: The stretching behavior of droplet dispersions with viscosity different from the matrix fluid is examined in chaotic and regular flows, in the limit of zero interfacial tension. Computations use a Lagrangian particle method, with the microstructure for each particle based on an exact solution for ellipsoidal droplets in the dilute limit. Two closed, two-dimensional time-periodic flows are considered: flow between eccentric cylinders and the sine flow. In regular flows with viscosity ratio of five or greater, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Except for case F, tracer s 1 is folded and stretched when wandering around whole screw channel. From top and front views, we could draw the conclusion that the mixing patterns were distinct from the previous research results because of the very large geometric ratio we used . With the increase of the geometric ratio, tracer covered less z distance.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Except for case F, tracer s 1 is folded and stretched when wandering around whole screw channel. From top and front views, we could draw the conclusion that the mixing patterns were distinct from the previous research results because of the very large geometric ratio we used . With the increase of the geometric ratio, tracer covered less z distance.…”
Section: Resultsmentioning
confidence: 56%
“…After that, numerous studies focused on investigating the mechanism and quantification of chaotic mixing in different models and on finding ways to achieve more efficient chaotic mixing in engineering application . To understand chaotic mixing, various techniques from mathematics and physics, such as Poincaré maps, periodic point analysis, tracer stretching distributions, and so on, are used. Along with the significant advances in chaotic mixing in two‐dimensional periodic flows, the perturbative theory of mixing for three‐dimensional steady flows was initiated by Feingold et al and Mezić and Wiggins and some applications were found .…”
Section: Introductionmentioning
confidence: 99%
“…Other models by Muzzio et al (1992) and Florek and Tucker (2005) are excellent for describing the stretching of the droplet morphology in globally chaotic flows. However, these models neglect interfacial tension and thereby omit breakup and coalescence events.…”
Section: Problem Description and Mesh Convergencementioning
confidence: 99%